Students` Response Toward Facebook as A Media in Learning Bahasa Indonesia - Hayu Afdetis Mana, Lira (International Journal of Language Pedagogy, 2021)
A tedious situation of learning Indonesian in pandemic era makes Facebook become a choice to have a interesting learning process. The purpose of this research is to see students' responses to Facebook as a learning medium. This is a descriptive qualitative research. The instrument used in this research was students` response questionnaires to Facebook as a learning medium which was distributed to 145 high school students in West Sumatra by using the google form. The results of this study shows that students: [1] have used Facebook; [2] saw Facebook as a positive, profitable and entertaining application; [3] (minority) saw Facebook as a negative and unsatisfactory application; [4] like Facebook because they can get information; [5] mostly agree that the Facebook application is used as a medium for learning Indonesian [6] (minority) do not like to use Facebook due to many naughty accounts appear; [7] (mostly) have received information on procedural texts, short stories or narrative, explanatory, observation report, exposition, anecdotal, poetry and negotiation. Then, [8] (minority) have never seen texts debates, saga, novels, dramas, lectures. Hence, it can be concluded that Facebook can be used as a learning medium to make the students motivated and enjoyed the learning process.